TAMAN PATUNG TERAKOTA PENARI GANDRUNG DI BANYUWANGI JAWA TIMUR - Yordan Putra Bintoro; I Ketut Sudita; I Gusti Ngurah Sura Ardana (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
This research of the terracotta gandrung dancer statue in Banyuwangi, East Java is “rawat ruwat” site in the cultural tradition of the Banyuwangi community to describe (1) the history of terracotta gandrung dancer statue garden in Banyuwangi East Java, (2) the Value, Symbol as well as The meaning of gandrung dancer statue garden in Banyuwangi East Java, (3) the setting of gandrung dancer statue garden in Banyuwangi East Java, (4) Process And Technique of terracotta gandrung dancer statue in Banyuwangi East Java. The type of this study is descriptive qualitative. The object study is the terracotta gandrung dancer statue garden in Banyuwangi, East Java. The method of data collection is used observation, interviews, and documentation. The results of this study is as following: the history of the terracotta gandrung dancer statue is as a care site ruwat on culture Banyuwangi to change era. Symbols and the meaning on terracotta gandrung dancer statue is jejer, ngepren , seblang subuh and also the available makda clothes gandrung that is omprok , kelat bahu, pattern of gajah oling. Setting the garden statue terracotta gandrung dancer forms the latter T, forming circular, vertical or straight. Manufacturing process garden statue terracota gandrung dancer use Technique print or cast in making statue terracotta gandrung dancer and the combustion process. Keywords: garden, terracotta, statue, gandrung